2020
DOI: 10.1038/s41396-020-00837-2
|View full text |Cite
|
Sign up to set email alerts
|

Metagenomic analysis reveals a dynamic microbiome with diversified adaptive functions to utilize high lignocellulosic forages in the cattle rumen

Abstract: Rumen microbiota play a key role in the digestion and utilization of plant materials by the ruminant species, which have important implications for greenhouse gas emission. Yet, little is known about the key taxa and potential gene functions involved in the digestion process. Here, we performed a genome-centric analysis of rumen microbiota attached to six different lignocellulosic biomasses in rumen-fistulated cattle. Our metagenome sequencing provided novel genomic insights into functional potential of 523 un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
70
2
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 127 publications
(82 citation statements)
references
References 75 publications
8
70
2
2
Order By: Relevance
“…), Ruminococcaceae, Spirochaetaceae (Treponema spp.) (Vital et al, 2015;Gharechahi et al, 2020;Vacca et al, 2020) and Rikenellaceae (Vital et al, 2015). The bioavailability of butyrate is obviously related to endurance performance because of the role played by this molecule in energy metabolism (Mollica et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…), Ruminococcaceae, Spirochaetaceae (Treponema spp.) (Vital et al, 2015;Gharechahi et al, 2020;Vacca et al, 2020) and Rikenellaceae (Vital et al, 2015). The bioavailability of butyrate is obviously related to endurance performance because of the role played by this molecule in energy metabolism (Mollica et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…The results show that Firmicutes and Bacteroides are dominant and their sum of relative abundance reached more than 90% in the intestine of Suhuai pigs ( Figure 1 ), which is consistent with the research of Adhikari et al (2019) on PIC genetics nursery pigs and the research of Niu et al (2019 , 2020) on Sutai pigs and Suhuai pigs. Previous studies have found that Firmicutes and Bacteroides were capable of degrading many carbohydrate polymers in different ruminants, including cattle ( Stewart et al, 2018 , 2019 ; Gharechahi et al, 2021 ), camels ( Gharechahi and Salekdeh, 2018 ), and moose ( Svartström et al, 2017 ). The proportion of Firmicutes in the intestinal tract of pigs with low digestibility (L_NDF: 85.85%; L_ADF: 86.31%) was higher than that of high digestibility (H_NDF: 79.88; H_ADF: 78.76%) and the proportion of Bacteroidetes in the intestinal tract of pigs with high digestibility (H_NDF: 12.14%; H_ADF: 12.08%) was higher than that of low digestibility (L_NDF: 7.16%; L_ADF: 6.89%), which indicated that the community competition between Firmicutes and Bacteroidetes may be related to the fiber degradation ability of pigs ( Figure 1 ).…”
Section: Discussionmentioning
confidence: 99%
“…), Ruminococcaceae , Spirochaetaceae ( Treponema spp.) (Vital et al , 2015; Vacca et al , 2020; Gharechahi et al , 2020) and Rikenellaceae (Vital et al , 2015). The bioavailability of butyrate is obviously related to endurance performance because of the role played by this molecule in energy metabolism (Mollica et al , 2017).…”
Section: Discussionmentioning
confidence: 99%